The Sep1 Mutant of Saccharomyces Cerevisiae Arrests in Pachytene and Is Deficient in Meiotic Recombination - Tishkoff, D. X. (1995)
Strand exchange protein 1 (Sep1) from Saccharomyces cerevisiae promotes homologous pairing of DNA in vitro and sep1 mutants display pleiotropic phenotypes in both vegetative and meiotic cells. In this study, we examined in detail the ability of the sep1 mutant to progress through meiosis I prophase and to undergo meiotic recombination. In meiotic return-to-growth experiments, commitment to meiotic recombination began at the same time in wild type and mutant; however, recombinants accumulated at decreased rates in the mutant. Gene conversion eventually reached nearly wild-type levels, whereas crossing over reached 15-50% of wild type. In an assay of intrachromosomal pop-out recombination, the sep1, dmc1 and rad51 single mutations had only small effects; however, pop-out recombination was virtually eliminated in the sep1 dmc1 and sep1 rad51 double mutants, providing evidence for multiple recombination pathways. Analysis of meiotic recombination intermediates indicates that the sep1 mutant is deficient in meiotic double-strand break repair. In a physical assay, the formation of mature reciprocal recombinants in the sep1 mutant was delayed relative to wild type and ultimately reached only 50% of the wild-type level. Electron microscopic analysis of meiotic nuclear spreads indicates that the sep1δ mutant arrests in pachytene, with apparently normal synaptonemal complex. This arrest is RAD9-independent. We hypothesize that the Sep1 protein participates directly in meiotic recombination and that other strand exchange enzymes, acting in parallel recombination pathways, are able to substitute partially for the absence of the Sep1 protein.